Aplikasi kamus kebidanan berbasis Android - hariati Husain (Jurnal Informatika Upgris, 2019)
The development of smartphones often makes students abandon the habit of reading books. Many dictionary books the term midwifery is outstanding but it actually feels difficult and time consuming. Manual search is one reason why reading a dictionary is the last choice compared to searching through the Google search engine. No doubt the existence of smartphone technology, all information is growing very quickly. For this reason, a midwifery dictionary application is needed to make it easier for users to understand the meaning of words and midwifery terms. The dictionary must be easily used by smartphone users for this application.